Chronic pain in the thoracic spine as a symptom of multiple myeloma - case report - Kamila Woźniak; Dorota Ratuszek-Sadowska; Mateusz Szostak; Agnieszka Nowacka; Maciej Śniegocki (Kazimierz Wielki University, 2017)
Multiple myeloma is a hematological cancer, characterized by the neoplastic proliferation of a single clone of plasma cell producing a monoclonal protein. The incidence of multiple myeloma increases with age. The median age ad diagnosis is between 63 and 70 years old. The major clinical manifestations of multiple myeloma are related to loss of bone. This bone loss often leads to pathologic fractures, spinal cord compression, hypercalcemia and bone pain. Other symptoms of multiple myeloma are anaemia, leucopenia, thrombocytopenia, hyperproteinemia with decreased serum albumin, elevated serum C-reactive protein (CRP) and kidney dysfunction. Patients suffer from multiple myeloma often require analgesics, such as paracetamol and weak or strong opioids, but nonsteroidal anti-inflammatory drugs (NSAIDS) are contraindicated. The authors presents a case of the 62-years old man with myeloma multiple, who had chronic pain in the thoracic spine, nonspecific laboratory findings: macrocytic anaemia, without hypercalcemia and elevated serum CRP. Kidney function was normal.